Stable Bilateral Teleoperation Control Method for Biped Robots with Time-Varying Delays. (8th February 2023) - Moya, Viviana; Slawiñski, Emanuel; Mut, Vicente; Chávez, Danilo; Wagner, Bernardo
Abstract : This document proposes a control scheme applied to delayed bilateral teleoperation of the forward and turn speed of a biped robot against asymmetric and time-varying delays. This biped robot is modeled as a hybrid dynamic system because it behaves as a continuous system when the leg moves forward and discrete when the foot touches the ground generating an impulsive response. It is proposed to vary online the damping according to the time delay present in the communication channel, and the walking cycle time using an optimization criterion, to decrease the teleoperation system errors. To accomplish this, a three-phase cascade calibration process is used, and their benefits are evidenced in a comparative simulation study. The first phase is an offline calibration of the inverse dynamic compensation and also the parameters of the bilateral controller. The second phase guarantees the bilateral coordination of the delayed teleoperation system, using the Lyapunov–Krasovskii stability theory, by changing the leader damping and the equivalent follower damping together. The third phase assures a stable walk of the hybrid dynamics by controlling the walking cycle time and the real damping to move the eigenvalues of the Poincaré map, numerically computed, to stable limit cycles and link this result with an equivalent continuous system to join both phases. Additionally, a fictitious force was implemented to detect and avoid possible collisions with obstacles. Finally, an intercontinental teleoperation experiment of an NAO robot via the Internet including force and visual feedback is shown.